Effects of intermittent seating upright, lower body negative pressure, and exercise on functional tasks performance after head-down tilt bed rest - Clément, Gilles; Moudy, Sarah C.; Macaulay, Timothy R.; Mulder, Edwin; Wood, Scott J. (Frontiers in Physiology, 2024)
Bed rest can be used as a ground-based analog of the body unloading associated with spaceflight. In this study, we determined how strict head-down tilt bed rest affects subjects' performance of functional tests (sit-to-stand, tandem walk, walk-and-turn, dynamic posturography) that challenge astronauts' balance control systems immediately after they return from space. Forty-seven participants were assessed before and a few hours after 30 days of 6° head down tilt bed rest at the DLR :envihab facility. During this bed rest study, called SANS-CM, the participants were divided into 4 groups that either (1) were positioned in headdown tilt continuously throughout the 30 days; (b) sat upright for 6 hours a day; (c) were exposed to lower body negative pressure (LBNP) for 6 hours a day; or (d) exercised for 60 minutes and then wore venous-occlusive cuffs for 6 hours a day. Results showed that strict head-down tilt bed rest causes deficits in performance of functional tasks that were similar to those observed in astronauts after spaceflight. Seated upright posture mitigated these deficits, whereas exercise or LBNP and cuffs partly mitigated them. These data suggest that more direct, active sensorimotor-based countermeasures may be necessary to maintain preflight levels of functional performance after a long period of body unloading.